Nest inundation from sea-level rise threatens sea turtle population viability. Issue 7 (July 2015) - Pike, David A.; Roznik, Elizabeth A.; Bell, Ian
Abstract : Contemporary sea-level rise will inundate coastal habitats with seawater more frequently, disrupting the life cycles of terrestrial fauna well before permanent habitat loss occurs. Sea turtles are reliant on low-lying coastal habitats worldwide for nesting, where eggs buried in the sand remain vulnerable to inundation until hatching. We show that saltwater inundation directly lowers the viability of green turtle eggs ( Chelonia mydas ) collected from the world's largest green turtle nesting rookery at Raine Island, Australia, which is undergoing enigmatic decline. Inundation for 1 or 3 h reduced egg viability by less than 10%, whereas inundation for 6 h reduced viability by approximately 30%. All embryonic developmental stages were vulnerable to mortality from saltwater inundation. Although the hatchlings that emerged from inundated eggs displayed normal physical and behavioural traits, hypoxia during incubation could influence other aspects of the physiology or behaviour of developing embryos, such as learning or spatial orientation. Saltwater inundation can directly lower hatching success, but it does not completely explain the consistently low rates of hatchling production observed on Raine Island. More frequent nest inundation associated with sea-level rise will increase variability in sea turtle hatching success spatially and temporally, due to direct and indirect impacts of saltwater inundation on developing embryos.